Ethnic Entrepreneurship, Social Capital, and Industry Dynamics: Insights from Real Estate and Finance Sectors - Kerimo, Feyyaz (Archives of Business Research, 2025)
This paper examines ethnic entrepreneurship in the real estate and finance sectors, focusing on the dynamics of social capital and the challenges and opportunities entrepreneurs face in these industries. It addresses two main questions: What are the barriers and drivers for ethnic entrepreneurs in real estate and finance, and how does social capital impact their success? Drawing from a multidisciplinary literature review, this study offers insights into the role of networks, institutional barriers, and cross-cultural business strategies. The findings provide practical implications for business leaders, policymakers, and researchers aiming to foster inclusive entrepreneurship and innovation in key economic sectors.